Analisis Perancangan Jig Machining Base Crankshaft Pulley Puller pada Mesin CNC Milling dengan Metode FMEA dan FTA di PT. XYZ - Hermawan Sriwindiarto (Universitas Islam Raden Rahmat, Malang, 2023)
“PT.XYZ operates in the manufacturing industry, including the production of jigs. Currently, there is an issue in the manufacturing process of the base Crankshaft pulley puller owned by PT.AHM on a CNC milling machine. The research aims to identify the types and causes of failures during production, as well as to provide recommendations for improvement and the design of machining jigs to PT.XYZ in order to eliminate failure rates, enhance efficiency, and effectiveness.Data processing methods used include Failure Mode and Effect Analysis (FMEA) and Fault Tree Analysis (FTA) supported by Pareto diagrams. The analysis results reveal several types of failures, with the highest Residual Risk Priority Number (RPN) being 384 for the first failure, followed by 360 for the second failure, 336 for the third failure, 294 for the fourth failure, and 240 for the fifth failure.The proposed improvement involves creating a jig with a clamping system using SCHUNK VERO-S and adding to its cavity. The results of the proposed improvement show better outcomes in terms of maintaining product quality and enhancing efficiency and effectiveness.”